Association between anti-nucleophosmin and anti-cardiolipin antibodies in (NZW × BXSB)F(1 )mice and human systemic lupus erythematosus - Lartigue, Aurelia (BioMed Central, 2005)
We showed previously that nucleophosmin (NPM), a nucleolar phosphoprotein, is recognized by sera from (NZW × BXSB)F(1 )(WB) mice, a model of systemic lupus erythematosus (SLE) and anti-phospholipid syndrome. In the present study we analysed the prevalence and kinetics of anti-NPM autoantibodies in WB mice by a solid-phase ELISA with recombinant human (rh) NPM as the antigen and showed that most male WB mouse sera had anti-NPM antibodies that were responsible for their indirect immunofluorescence staining pattern on Hep-2 cells. Anti-NPM antibodies were significantly associated with anti-cardiolipin (aCL) antibodies. This antibody profile mirrored that observed in certain human SLE sera because anti-NPM antibodies were detected in 28% of the sera from patients with SLE and were similarly associated with aCL antibodies. The demonstration that rhNPM bound to cardiolipin (CL) in vitro and increased the CL-binding activity of a WB-derived aCL monoclonal antibody indicates that NPM can interact with CL to form SLE-related immunogenic particles that might be responsible for the concomitant production of anti-NPM and aCL antibodies.